2018
DOI: 10.1155/2018/2032413
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Thyroid Hormones and Correlation of BMI with Thyroid Function in Healthy Zhuang Ethnic Pregnant Women

Abstract: Ethnic differences in the level of thyroid hormones exist among individuals. The American Thyroid Association (ATA) recommends that an institution or region should establish a specific thyroid hormone reference value for each stage of pregnancy. To date, a limited number of studies have reported the level of thyroid hormones in Chinese minorities, and the exact relationship between BMI and thyroid function in pregnant women is ill. This study was performed to establish trimester-specific reference ranges of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…In this study, based on the big clinical data collected from early pregnant women who delivered in the obstetrics and gynecology department of Peking Union Medical College Hospital, we established RIs of thyroid hormones for early pregnant women in China. Moreover, RIs for TSH and FT4 of early pregnancy in previous studies were listed, and our results concerning early pregnancy TSH and FT4 and FT3 RIs are comparable with those of other studies using the same detection platform [27,29]. However, the RIs for TSH and FT4 showed wide variation across studies and analytical systems, with the upper limit of TSH varying between 2.33 μIU/ml and 4.92 μIU/ml and the upper limit of FT4 varying between 1.18 ng/dl and 1.72 ng/dl.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, based on the big clinical data collected from early pregnant women who delivered in the obstetrics and gynecology department of Peking Union Medical College Hospital, we established RIs of thyroid hormones for early pregnant women in China. Moreover, RIs for TSH and FT4 of early pregnancy in previous studies were listed, and our results concerning early pregnancy TSH and FT4 and FT3 RIs are comparable with those of other studies using the same detection platform [27,29]. However, the RIs for TSH and FT4 showed wide variation across studies and analytical systems, with the upper limit of TSH varying between 2.33 μIU/ml and 4.92 μIU/ml and the upper limit of FT4 varying between 1.18 ng/dl and 1.72 ng/dl.…”
Section: Discussionsupporting
confidence: 89%
“…The TSH and FT4 RIs of early pregnant women as reported previously are shown in ▶ table 4 [25][26][27][28][29][30][31][32][33][34][35][36]. The RIs for TSH and FT4 of early pregnant women showed large differences across studies, and the RIs were different from detection platforms, ethnic and regions.…”
Section: Comparison Of Tsh and Ft4 Ris In Early Pregnant Individuals Across Previous Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Upon analysis of thyroid glands from electively terminated fetuses in the second trimester, Filis et al found significant changes in thyroid function, increased fetal thyroid mass and plasma TSH levels, and changes in the expression of genes critical for proper thyroid development based upon maternal BMI [ 30 ]. Another study conducted on Zhuang ethnic pregnant women did not find any statistically significant correlation between BMI and overt hypothyroidism, but a BMI > 25 was associated with a higher risk of overt hypothyroxinemia, defined as having a normal TSH with free T4 levels in the lower 2.5th percentile, based on the reference range for each trimester [ 31 ]. However, our study did not show any association between BMI and thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação a avaliação de correlação entre os valores de TSH e a idade, encontramos uma correlação não relevante estatisticamente (p=0,455; r=0,04). Na literatura recente, observamos uma replicação do resultado encontrado, não sendo identificadas alterações de dosagem sérica de TSH com relevância estatística relacionada à idade das gestantes em um estudo contendo 3324 gestantes (47).…”
Section: Resultados E Discussõesunclassified